2013
DOI: 10.1016/j.hoc.2013.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Immune Thrombocytopenia

Abstract: Immune thrombocytopenia (ITP) is a common hematologic disorder characterized by isolated thrombocytopenia. ITP presents as a primary form characterized by isolated thrombocytopenia (platelet count < 100 × 109/L) in the absence of other causes or disorders that may be associated with thrombocytopenia, or a secondary form in which immune thrombocytopenia develops in association with another disorder that is usually immune or infectious. ITP may affect individuals of all ages, with peaks during childhood and in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
173
0
11

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(186 citation statements)
references
References 127 publications
2
173
0
11
Order By: Relevance
“…is an orally bioavailable prodrug that is metabolized into a biologically active form, R406 (N4-2,2-dimethyl-3-oxo-4H-pyrid [1,4]oxazin-6-yl)-5-fluoro-N2-(3,4,5-trimethoxyphenyl)-2,4-pyrimidinediamine), a selective small molecule inhibitor of Syk (Figure 5) [31,46]. R406 was initially identified as a relatively specific inhibitor of Fc R-dependent mast cell activation in a cell-based screen for structure activity relationships with primary human mast cells [37].…”
Section: Spleen Tyrosine Kinase Inhibitionmentioning
confidence: 99%
See 3 more Smart Citations
“…is an orally bioavailable prodrug that is metabolized into a biologically active form, R406 (N4-2,2-dimethyl-3-oxo-4H-pyrid [1,4]oxazin-6-yl)-5-fluoro-N2-(3,4,5-trimethoxyphenyl)-2,4-pyrimidinediamine), a selective small molecule inhibitor of Syk (Figure 5) [31,46]. R406 was initially identified as a relatively specific inhibitor of Fc R-dependent mast cell activation in a cell-based screen for structure activity relationships with primary human mast cells [37].…”
Section: Spleen Tyrosine Kinase Inhibitionmentioning
confidence: 99%
“…In adults, the prevalence of ITP increases with age [6]. Some reports have suggested that incidence is slightly higher in women of reproductive age and the elderly [4,5].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Corticosteroids and IVIg are the first line therapy for ITP. 19 In our case, platelet transfusion was given in view of active bleeding. Also the ITP responded well to steroids and IV Immunoglobulins.…”
Section: Discussionmentioning
confidence: 85%